Biocompatibility of thermo‐responsive PNIPAAm‐PLLA‐PNIPAAm triblock copolymer as potential drug carrier. (29th June 2015) - Su, Feng; Shen, Xin; Hu, Yanfei; Darcos, Vincent; Li, Suming
Abstract : This work aims to evaluate the cytocompatibility and hemocompatibility of thermo‐responsive polymers as potential drug carrier. Thermo‐responsive poly( N ‐isopropyl acrylamide) (PNIPAAm) and poly( N ‐isopropyl acrylamide)‐poly(l ‐lactide)‐poly( N ‐isopropyl acrylamide) (PNIPAAm‐PLLA‐PNIPAAm) triblock copolymer were synthesized by atom transfer radical polymerization using ethyl α ‐bromoisobutyrate or Br‐PLLA‐Br as initiator under mild conditions. The self‐assembly and thermo‐responsive properties of the copolymer in aqueous medium were investigated by critical micelle concentration, dynamic light scattering, transmission electron microscopy, and lower critical solution temperature measurements. The critical micelle concentration was 0.014 mg ml −1 . Dynamic light scattering and transmission electron microscopy results show that the micelles are spherical in shape with sizes between 20 and 40 nm. The lower critical solution temperature of PNIPAAm and PNIPAAm‐PLLA‐PNIPAAm is 34.8°C and 32.8°C, respectively. 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay was carried out to evaluate the cytotoxicity of polymers, and the hemocompatibility was assessed from hemolysis ratio and plasma recalcification time measurements. The results show that PNIPAAm‐PLLA‐PNIPAAm presents outstanding biocompatibility and could be promising for applications in targeted drug delivery. Copyright © 2015 John Wiley & Sons, Ltd.